REINCIDÊNCIA DE GRAVIDEZ NA ADOLESCÊNCIA: Prevenção e cuidado - Castro, Priscila Mattos de (2017)
Adolescent pregnancy requires a more effective follow-up by health professionals, because this issue brings with it social, family and adolescent health demands and concomitant the child that comes.The objective of this research was to construct an informative primer emphasizing care for the prevention of gestational reincidência during adolescence.For this, an action research was carried out with a qualitative approach and the methodology of research in group care was used, which was developed from the care that took place in the discussions and conversations in a circle, providing a sensitive listening, expression of feelings, verbalization needs and the socialization of ideas.The sample consisted of 31 adolescents, aged 14 to 19 years, who participated weekly in meetings that lasted one hour and occurred in a Basic Health Unit and a Family Health Strategy in the municipality of Santa Maria, RS.The data were collected from July to September 2017, through a field diary in which the discussions that occurred at the meetings were recorded.From the analysis of the results four categories emerged: fragilities involving the environment of pregnancy in adolescence; lack of dialogue in the family; dropping out after the birth of the child; gestational reincidência.Watsan's theory was used as a theoretical reference for the discussion of the data. The adolescents involved in this research showed a promising look for adolescence with the ability to overcome early pregnancy and cases of gestational reincidência.It was emphasized the importance of participation and involvement of health professionals, school, together with families, in sexual prevention and education.The final product resulting from this research was an informative booklet, based on discussions and ideas of adolescents. This brings reality with its potentialities and weaknesses experienced during and after the gestation in adolescence.